Effectiveness in Cooling a Heat Sink in the Presence of a TPMS Porous Structure Comparing Two Different Flow Directions - Mohamad Ziad Saghir; Mohammad M. Rahman (Fluids)
The triply periodic minimal surface (TPMS) is receiving much interest among researchers. The advantage of using this TPMS structure is the ability to design a structure based on engineering need. In the present context, experimental measurement was conducted and compared with numerical models using a foam porous medium and TPMS porous structure, leading to an accurate calibration of the model. A porous medium, metal foam, was heated experimentally at the bottom, and forced convection was investigated for different heating conditions. Then, the porous foam was replaced with a TPMS, and the experiment was repeated under similar conditions. The experimental data were compared with the numerical model using COMSOL software. Besides the model’s accuracy, the TPMS showed a uniform heating condition contrary to the metal foam case. At a later stage, the numerical model was used to investigate the importance of flow direction (two flow directions) in cooling hot surfaces. The first flow was parallel to the hot surface, and the second perpendicular to the hot surface. The TPMS structure was located on the top of the hot surface and acted as a fin in both cases. The Nusselt number exceeded 80 in the presence of the TPMS. As the porosity of the TPMS decreases below 0.7, a more considerable pressure drop is observed. The performance evaluation criterion was found to be greater than 70 when the porosity of the TPMS structure was 0.8.